Exploring the Pathophysiology, Diagnosis, and Treatment Options of Multiple Sclerosis - Simone Lorenzut; Ilaria Del Negro; Giada Pauletto; Lorenzo Verriello; Leopoldo Spadea; Carlo Salati; Mutali Musa; Caterina Gagliano; Marco Zeppieri (Journal of Integrative Neuroscience)
The complicated neurological syndrome known as multiple sclerosis (MS) is typified by demyelination, inflammation, and neurodegeneration in the central nervous system (CNS). Managing this crippling illness requires an understanding of the complex interactions between neurophysiological systems, diagnostic techniques, and therapeutic methods. A complex series of processes, including immunological dysregulation, inflammation, and neurodegeneration, are involved in the pathogenesis of MS. Gene predisposition, autoreactive T cells, B cells, and cytokines are essential participants in the development of the disease. Demyelination interferes with the ability of the CNS to transmit signals, which can cause a variety of neurological symptoms, including impaired motor function, sensory deficiencies, and cognitive decline. Developing tailored therapeutics requires understanding the underlying processes guiding the course of the disease. Neuroimaging, laboratory testing, and clinical examination are all necessary for an accurate MS diagnosis. Evoked potentials and cerebrospinal fluid studies assist in verifying the diagnosis, but magnetic resonance imaging (MRI) is essential for identifying distinctive lesions in the CNS. Novel biomarkers have the potential to increase diagnostic precision and forecast prognosis. The goals of MS treatment options are to control symptoms, lower disease activity, and enhance quality of life. To stop relapses and reduce the course of the disease, disease-modifying treatments (DMTs) target several components of the immune response. DMTs that are now on the market include interferons, glatiramer acetate, monoclonal antibodies, and oral immunomodulators; each has a unique mode of action and safety profile. Symptomatic treatments improve patients' general well-being by addressing specific symptoms, including pain, sphincter disorders, fatigue, and spasticity. Novel treatment targets, neuroprotective tactics, and personalized medicine techniques will be the main focus of MS research in the future. Improving long-term outcomes for MS patients and optimizing disease treatment may be possible by utilizing immunology, genetics, and neuroimaging developments. This study concludes by highlighting the complexity of multiple MS, including its changing therapeutic landscape, diagnostic problems, and neurophysiological foundations. A thorough grasp of these elements is essential to improving our capacity to identify, manage, and eventually overcome this intricate neurological condition.